Step-by-step challenge of debris characterization for the decommissioning of Fukushima-Daiichi Nuclear Power Station (FDNPS). Issue 7 (3rd July 2022) - Kurata, Masaki; Okuzumi, Naoaki; Nakayoshi, Akira; Ikeuchi, Hirotomo; Koyama, Shinichi
Abstract: The present article reviewed the step-by-step attempts on debris characterization after the severe accident of Fukushima-Daiichi Nuclear Power Station (FDNPS). It was rather difficult to investigate the reactor inside in the first few years. Distribution of degraded core materials, i.e. fuel debris, was investigated by a muon tomography and the damaged reactor status was preliminarily predicted from the severe accident analysis. In parallel, literature review was carried out for the debris generated after Three Mile Island unit 2 accident and the simulated debris previously examined in the nuclear safety research. Since 2017, remote investigations of the reactor inside have been carried out, which is gradually clarifying the damage status. The sample analysis has accumulated useful knowledge for the debris characterization. Furthermore, several out-of-pile tests which reflected unique accident conditions at the FDNPS have been conducted mainly in Japan, including characterization of simulated ex-vessel debris, formation mechanism of metal-rich debris and debris corrosion by seawater materials. To establish a proper analysis method suitable for debris samples is also extremely important. These accumulated knowledge and data have been reviewed and compiled as a database 'debrisWiki' in Japan, which includes core status maps, investigation results of the reactor inside, probable accident scenarios, sample analysis data and so on. Various international collaborations were launched and several have continued for the decommissioning of the FDNPS and the use of relevant knowledge for improving the nuclear safety. Graphical abstract: uf0001